Disencontro: an analysis of narrative space from Existentialist Philosophy (Research, Society and Development, 2020)
This article aims to analyze the space in the work Des/encontro, by the writer João Uilson Vieira Filho, for this it will be up to investigate how the narrator describes the aspects related to anguish in the life of the character Lancimar, to verify how aspects of the past influence the daily life of the character thus contributing to a life of distress and, to ascertain how Lancimar manages to overcome the attitudes of bad faith, thus assuming his actions in front of life. We will use the bibliographic research method, in works of authors who have already studied and deepened the subject and as a theoretical contribution to the description of the space the work Poetics of the Literary Space, by Oziris Borges Filho and for the analysis of existentialism the book O Ser e o Nada by the philosopher Jean-Paul Sartre. We believe that success succeeds overcome bad faith and live authentic.